2009
DOI: 10.1111/j.1553-2712.2009.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicant Considerations Associated with Selection of an Emergency Medicine Residency Program

Abstract: Objectives: The primary objective of this study was to assess variables that residency applicants ranked as influential in making residency choices. The secondary objective was to determine if residents were satisfied with their residency choices.Methods: A secondary analysis was performed on a cohort database from a stratified, random sampling of 322 emergency medicine (EM) residents collected in 1996-1998 and 2001-2004 from the American Board of Emergency Medicine Longitudinal Study on Emergency Medicine Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
(4 reference statements)
1
18
0
Order By: Relevance
“…A prior study in internal medicine applicants found diversity to be an important program factor to minority applicants; however, the current study did not. 7 Perhaps our minority applicants view geographic location as a more important indicator of diversity than factors within individual programs? Further exploration of why this important group favors geographic location is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A prior study in internal medicine applicants found diversity to be an important program factor to minority applicants; however, the current study did not. 7 Perhaps our minority applicants view geographic location as a more important indicator of diversity than factors within individual programs? Further exploration of why this important group favors geographic location is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…That residency training is about education and not financial gain is a recurrent theme in studies involving applicants to EM programs, as well as other specialties. 1,7,8,10,11 Although salary and benefits consistently rank as a relatively unimportant factor, decision-making in training program selection is a multi-factorial process. Consequently, lesser priority factors should not be disregarded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 This finding could relate to the limited variability in salaries and benefits among programs nationally, making this a less useful discriminating factor. 19 Also, applicants in this study rated the importance of health care benefits higher than they did salary, which may reflect the high cost of health insurance and a growing number of residency applicants with dependents. 17 The literature is unclear about the effect of sex on residency program choice.…”
Section: Categorization Of Specialtiesmentioning
confidence: 99%